The active functional microbes contribute differently to soil nitrification and denitrification potential under long-term fertilizer regimes in North-East China - Wang, Feng; Liang, Xiaolong; Ding, Fan; Ren, Lingling; Liang, Minjie; An, Tingting; Li, Shuangyi; Wang, Jingkuan; Liu, Lingzhi (Frontiers in Microbiology, 2022)
Nitrogen (N) cycling microorganisms mediate soil nitrogen transformation processes, thereby affecting agricultural production and environment quality. However, it is not fully understood how active N-cycling microbial community in soil respond to long-term fertilization, as well as which microorganisms regulate soil nitrogen cycling in agricultural ecosystem. Here, we collected the soils from different depths and seasons at a 29-year fertilization experimental field (organic/chemical fertilizer), and investigated the transcriptions of N-cycling functional genes and their contribution to potential nitrification and denitrification. We found that long-term fertilization exerted significant impacts on the transcript abundances of nitrifiers (AOA amoA, AOB amoA and hao) and denitrifiers (narG and nosZ), which was also notably influenced by season variation. The transcriptions of AOA amoA, hao and narG genes was lowest in autumn, and AOB amoA and nosZ transcript abundances were highest in autumn. Compared to no fertilization, soil potential nitrification rate (PNR) was reduced in fertilization treatments, while soil potential denitrification rate (PDR) was significantly enhanced in organic combined chemical fertilizer treatment. Both PNR and PDR were highest in 0-20cm among the tested soil depths. Path model indicated active nitrifiers and denitrifiers had significant impact on soil PNR and PDR respectively. The transcriptions of AOA amoA and nxr genes were significantly correlated with soil PNR (Pearson correlation, r > 0.174, P < 0.05). Significant correlation of napA and nosZ transcriptions with soil PDR (Pearson correlation, r > 0.234, P < 0.05) was also revealed. Random forest analysis showed that SOC content and soil pH were the important factors explaining the total variance of active nitrifers and denitrifiers, respectively. Taken together, long-term fertilization regimes reduced soil PNR and enhanced PDR, which could be attributed to the different responses of active N-cycling microorganisms to soil environment variations. This work provides new insight into the nitrogen cycle, particularly microbial indicators in nitrification and denitrification of long-term fertilized agricultural ecosystems.